An energy aware data aggregation in wireless sensor network using connected dominant set - Santhoshkumar, P.; Suganthi, K. (International Journal of Engineering and Technology, 2019)
The technological progress in various domains has enabled the formulation of Wireless Sensor Networks (WSN). These areas include highly integrated digital circuits, low energy consumption processors, wireless communications among the others. For de-creasing the energy consumed in data communication, some of the superfluous data is eliminated during data aggregation. One of the most famous protocols based on hierarchy and which factors routing in WSNs is Low Energy Adaptive Clustering Hierarchy (LEACH). Among various improvisations suggested for LEACH, the stable election protocol is one of them .For improving the performance of the WSNs, the virtual backbone of the network is formulated by A Connected Dominating Set (CDS) of a graph. This work factors the formulation of clusters based on CDS. This technique has been contrasted with LEACH.Â Â